Evaluation of conflict of land use in the Lamarão river watershed, Federal District - Souza, João Maurício Fernandes (2019)
The lack of studies and the constant degradation of Permanent Preservation Areas (PPA’s) have represented one of the biggest barriers to the planning of conservation actions, in addition to promoting the use of inappropriate strategies for watershed management. Thus, the objective of was study map the land use, to automatically delimit the PPA’s and to identify the occurrence of conflicts in land use, having as legal reference, the Brazilian Forest Code and Resolution No. 303, of CONAMA. The research has developed in the watershed of the Lamarão stream, located in the southeast of the Federal District, Brazil. For the land use classification, a digital image of the ALOS satellite with 10 - meter spatial resolution, AVNIR - 2 sensor, obtained in July 2010 has used. The relief and hydrography data used were obtained in digital format on a scale of 1: 10,000. It was possible to map seven land use classes: exposed soil (1.01%); agriculture (50.46%); sparse cerrado (11.28%); cerrado dense (10.45%); pasture (17.54%); central pivot (7.63%); and clouds (1.55%). The PPA’s located in the upper third of hills (9.94 km²); springs and their respective contributing areas (0.27 km²); riparian zones with width less than 10 meters (24.10 km²), summing 34.31 km² (36.85%). There were no identified PPA’s on hillsides with slopes greater than 45°. The area of undue use corresponded to 21.70 km² (63.24%), with agriculture (38.40%) and pasture (15.32%) classes occupying most of this area. Only 11.50 km² (33.46%) of PPA’s are protected by native vegetation.